Navegando hacia mi playa: The Sea as Representation of Longing and Return in Raquel Ilombé’s Poetry - El, Diego Gutierrez (Research in African literatures, 2025)
Exile, nostalgia, and unhomeliness appear as recurring themes within Equatorial Guinean literature, which has been heavily shaped through texts that portray the experience of the diaspora. Within this tradition, the poetry of Raquel Ilombé (1938–92) appears as a fundamental example of how diasporic Equatoguinean identity is represented in literature. Throughout Raquel Ilombe’s poetic work, the sea appears as an ambivalent image that represents both the longing for the motherland and the impossibility of return. Through the shifting signification of the sea, Ilombé’s poetry presents a fluctuating identity through which the anxieties of exile become apparent. The purpose of this article is to analyze the way in which, across Ilombe’s oeuvre, the sea incarnates feelings of longing, hope, and helplessness alike, therefore portraying the tensions of diasporic identity. These devices, in turn, form and influence an Equatoguinean literary canon that has often been underexplored and whose traditions of depicting the experience of liminality provide a window into the sensibilities of the migratory experience.